1. Let A be a square matrix of order 2. Prove that A satisfies the equation A2 - trace(A)A + det(A)I = 0, where trace(A) = a + d, det(A) = ad - bc, and I is the 2x2 identity matrix.

If we define A to be general matrix of order 2:

> with(linalg):A:=matrix(2,2,[[a,b],[c,d]]);
A := [ a b ]
[ c d ]

then we may simply substitute this and the given values for trace(A) and det(A) into the above equation. Define the left hand side:

> LHS:=evalm(A^2-(a+d)*A+(a*d-b*c));
A := [ a2 + (- a - d) a + a d a b + b d + (- a - d) b ]
[ c a + d c + (- a - d) c d2 + (- a - d) d + a d ]

We need to simplify this matrix. Here's how:

> for i from 1 to 2 do for j from 1 to 2 do LHS[i,j]:=simplify(LHS[i,j]) od od;
> evalm(LHS);
[ 0 0 ]
[ 0 0 ]

Since we may take 0 to mean the zero matrix, the two sides of the equation are equivalent:

0 = 0
A2 - (a + d)A + (ad - bc)I = 0
A2 - trace(A)A + det(A)I = 0.


2. Prove that, if A is a 2x2 matrix and An = 0 for some natural number n, then A2 = 0.

From the above problem we can state that A2 = bA + cI if we use the equality A2 = trace(A)A - det(A)I and let b = trace(A) and c = (-det(A)).

Now, we need to show that c = 0. To do this we assume that A is invertible. Since A-1 exists, we may multiply the equation An = 0 by (A-1)n = A-n:

(An)(A-n) = 0(A-n) => An-n = 0 => A0 = 0 => I = 0

This equation clearly indicates a contradiction. So we conclude that A cannot be invertible. Now assume that c is not 0. The equation A2 - bA = cI can be rearranged divided by c. The result is the following: (1/c) * (A2 - bA) = I. Utilizing the definition of the identity matrix and associativity, we know A = AI => bA = bAI => bA = bAI. With this new knowledge, we can rewrite this equation as such: (1/c) * A(A - bI) = I. By the definition of an inverse, A - bI has to be equal to c * (A-1). For this to be true, the matrix A would have to invertible which we proved is not the case. Therefore our assumption is wrong and c = 0, so now we can say that A2 = bA.

If we multiply both sides of A2 = bA by An-2 we achieve the new equation

An = bAn-1. (1)


By substituting n-1 into equation (1) for n we get the equation: An-1 = bAn-1-1 => An-1 = bAn-2. By substituting this new value of An-1 into equation (1), we acquire

An = b(bAn-2) =(b2)*(An-2). (2)


By substituting n-2 for n into equation (1), we get An-2 = b(An-3). Substituting this value of An-2 into equation (2), we get

An = (b2)*b(An-3) = An = (b3)*(An-3). (3)


A pattern is evident:

An = b(An-1) = (b2)(An-2) = (b3)(An-3) = . . . = (bn-2)(A2).

We are given that An = 0, hence (bn-2)(A2) = 0. We conclude that either bn-2 = 0 or A2 = 0. If A2 = 0 then we have concluded our proof. If bn-2 = 0 and we multiply both sides of the equation by b3-n we get (bn-2) * (b3-n) = (b3-n) * 0 => b = 0. Then A2 = bA = 0 in this case also.

3. Find a square 3 x 3 matrix such that A3 is zero but A2 is not zero.

If A is the following matrix:

> A:=matrix(3,3,[[0,1,0],[1,0,1],[0,-1,0]]);
A := [ 0 1 0 ]
[ 1 0 0 ]
[ 0 -1 0 ]

Then A3 is the zero matrix as shown below:

> evalm(A^3);
[ 0 0 0 ]
[ 0 0 0 ]
[ 0 0 0 ]

A2 is not the zero matrix though:

> evalm(A^2);
[ 1 0 1 ]
[ 0 0 0 ]
[ -1 0 -1 ]